Macrocyclic complexes of Pt(ii) and Rh(iii) with iso-tellurazole N-oxides. Issue 15 (20th March 2019) - Ho, Peter C.; Bui, Robert; Cevallos, Alberto; Sequeira, Shanel; Britten, James F.; Vargas-Baca, Ignacio
Abstract : Tetramers of iso-tellurazole N -oxides form stable macrocyclic complexes with Pt(ii ) and Rh(iii ) in solution. Abstract : Pt(ii ) and Rh(iii ) readily form complexes with 3-methyl-5-aryl-1, 2-tellurazole 2-oxides (L = (3-Me-5-Ar-1, 2-C3 HTe(NO)). The aryl group is either phenyl or 3, 5-di- tert -butylphenyl, the latter case being a new derivative with enhanced solubility. The compound [Pt(3-Me-5-(3, 5- t Bu2 C6 H3 )-1, 2-C3 HTe(NO))4 ](BF4 )2 crystallizes in the P 21 / C space group featuring a square planar complex in the lattice. The crystal of [RhCl2 (3-Me-5-(C6 H5 )-1, 2-C3 HTe(NO))4 ](BF4 ) belongs to the I 4̄ space group and contains an octahedral complex. In both instances, the iso-tellurazole N -oxide molecules are linked by Te⋯O chalcogen bonding interactions confirming an annular tetramer that binds the metal ion as a κ 4 Te macrocycle in a boat conformation. Low-frequency shifts of the 125 Te magnetic resonance upon coordination and the observation of 125 Te– 195 Pt and 125 Te– 103 Rh 1 J coupling constants indicate that the complexes are stable species in solution. The complex ions were also observed in the electrospray mass spectra.